INDONESIA AND LGBT: IS IT TIME TO APPRECIATE LOCAL VALUE? - Rima Yuwana YUSTIKANINGRUM (Challenges of the Knowledge Society)
This article addresses the issue on why Indonesian people cannot accept Lesbian, Gay, Bisexual, and Transgender (“LGBT”). Further, it also illustrates the reflection on how the society changes paradox in the era of globalisation. More concretely, which shows its willingness to uniform the social structure, at the same time attempts to preserve their own distinctive identity. Indonesian people who uphold Pancasila or five national ideologies would be a perfect example in this case. Pancasila, in this case, is a crystallization form of the values such as religious, social, and cultural realm which live within Indonesian society. As time passes, Pancasila is often grounded and contrasted to western cultural values like LGBT. The influx of LGBT thoughts which relies on the human rights concept spread a long time ago in Indonesia. However, this issue reemerges into the air, at the same time in different places and countries, becomes the vast spread of LGBT legalization such as in Europe and America. The resistance against Indonesian people, who mostly anti LGBT concept, is sparked by the influence of international human right law. These are recorded several times in Indonesia’s history. Attempts such as submitting judicial review in the Constitutional Court about the offense of adultery contained in the criminal law case, establishing the pro-LGBT legal communities, and gathering social supports are also conducted to convince Indonesian people to accept LGBT in the society. However, both society and government agree to take steps and synergize to stand firmly to drown this effort. Then, this article will also expose some scholars’ arguments, cases, jurisprudence, and journals to show the authors’ standing in this context.